2019
DOI: 10.1177/0272989x19875950
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Survival Curve Extrapolation Techniques Using Long-Term Observational Cancer Data

Abstract: Objectives. Uncertainty in survival prediction beyond trial follow-up is highly influential in cost-effectiveness analyses of oncology products. This research provides an empirical evaluation of the accuracy of alternative methods and recommendations for their implementation. Methods. Mature (15-year) survival data were reconstructed from a published database study for “no treatment,” radiotherapy, surgery plus radiotherapy, and surgery in early stage non–small cell lung cancer in an elderly patient population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Real-world data may come from other distributions or may not be well represented by a parametric curve. Similarly, it is unclear whether alternatives to parametric modeling, such as combining trial data with external data 16 or using Bayesian model averaging, 17 may improve RMST predictions.…”
Section: Limitationsmentioning
confidence: 99%
“…Real-world data may come from other distributions or may not be well represented by a parametric curve. Similarly, it is unclear whether alternatives to parametric modeling, such as combining trial data with external data 16 or using Bayesian model averaging, 17 may improve RMST predictions.…”
Section: Limitationsmentioning
confidence: 99%
“…According to Kim and Prasad (2015), who followed up on the survival improvement of drugs approved based on the surrogate endpoint at the time of FDA approval (median follow-up 4.4 years), only 5 out of 36 cases demonstrated survival gain ( Kim and Prasad, 2015 ). However, few efforts have been made to assess the validity of survival predictions compared to actual data ( Latimner, 2013 ; Vickers, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is controversial whether the clinical bene ts of surgical treatment are signi cant for older patients even if their NSCLC is at an early stage, such as stage IB. Although there have been a few studies exploring the advantages and disadvantages of surgical treatment in older patients with early-stage NSCLC, these studies have the insu cient sample size and interference of confounding factors [18,19]. Our results showed that there was a severely unbalanced distribution of clinicopathological characteristics between the surgical and non-surgical groups, although surgical treatment was the most signi cant protective factor among all the clinical factors for both OS and DSS (Figure S1-2, Table 1).…”
Section: Discussionmentioning
confidence: 99%